Two-dimensional exciton behavior in GaN nanocolumns grown by molecular-beam epitaxy - Na, J; Taylor, R; Rice, J; Robinson, J; Lee, K; Park, Y; Park, C; Kang, T (American Institute of Physics, 2005)
We have investigated the behavior of excitons in GaN nanocolumns using time-integrated and time-resolved micro-photoluminescence measurements. In the weak confinement limit, the model of fractional-dimensional space gives an intermediate dimensionality of 2.14 for GaN nanocolumns, with an average diameter of 80 nm. Enhanced exciton and donor binding energies are deduced from a fractional-dimensional model and a phenomenological description. Time-integrated photoluminescence spectra as a function of temperature show a curved emission shift. Recombination dynamics are deduced from the temperature dependence of the PL efficiency and decay times.